School Textbook as a Source of Study of Differentiation of Content of Social Science Subjects (40 – 50s of ХХ Century) - Nestor Gupan (Pedagogical Discourse, 2013)
The article deals with the questions of study differentiation by means of school textbook in 40-50s of the XX century. Changes in the national textbooks making in the context of changes in the educational paradigm are explained. Directions of external differentiation by the age peculiarities of pupils and national needs of pupils in the USSR are examined.